Virus Defektif Hepatitis D Satelit Subviral Hepatitis B - Donna Mesina R. Pasaribu (Jurnal Kedokteran Meditek, 2011)
AbstrackHepatitis delta virus (HDV) was isolated from liver biopsy of a person with chronic HBs Ag. HBV virions and virions with delta antigen are pathogenic and very infectious. HDV is considered as a subviral satellite because of their distribution in hepatocyte cells only in the presence of HBV. Deltavirus is an incomplete RNA virus (defevtive virus), because HDV can not cause infection, for the occurrence of an HDV infection of HBV infection should occur before or at the time together. HDV genome is a circular singel-stranded RNA of negative polarity, consisting of 1700 nucleotides and did not reveal any homology with HBV genome. Spherical-shaped virion particle size 36 nm is a component of the outer, diencapsidasi by HBsAg (the envelope) and the inside of the nukeokapsid consists of 60 copies of genomic delta antigen (Dane particles). clinical manifestations of infection depends on the virulence of HBV HDV. On a carrier of HBV infection, who had superinfection, HDV does not depend on the manifestation of HBV. Modes of transmission similar to HBV, infection most often is the intravenous drug abusers. The prevalence of HDV is not always a picture of the prevalence of HBV. In Indonesia,73 reported hepatitis B carriers who donate blood anti-HDV positive 2.7%. Prevention of infection is the prevention of HBV infection, it also indirectly prevent the transmission of HDV. Precautions are taken with HBsAg vaccination.Key word : HDV, Defective virus, Dane particle